The economic and social foundations of European civilization - Dopsch, Alfons (Routlege & Kegan Paul, 1937)
This book is a translation in a somewhat shortened form of the second edition of my german work, die wirstchaftlichen und sozialen grundlagen der Europaischen kulturentwicklung, which was published in Vienna in 1923-4